259 Use of internet connected cloud devices in stroke rehab-experience with a patient. Issue 12 (14th November 2019) - Dey, K; Das, S
Abstract : We provided Alexa devices-Amazon Echo Show and Echo Spot to a 56- year old patient recovering from an ischaemic stroke at home. Amazon Echo device is a WiFi connected device driven by Alexa, a voice assistant. We trained our patient on the use and control of the devices using her voice and provided technical know how. Once set up, she was able to use the voice control to perform several tasks- listening to news listening to music and radio playing sounds for meditation turning on and off lights setting up alarms for medications setting up times for doing scheduled exercise making hands free phone calls This was especially useful when her carer was not present by her side. Later on we added Amazon cloud cam to the set up so that family members could remotely monitor her activity. She was able to make the physiotherapy sessions fun and interesting with the help of apps running on the devices upon voice prompts. In the emerging economies the joint family structure is breaking down. The relatives working as informal carers are disappearing fast. The main care is often provided by the privately hired nurses or health care assistants provided by local agencies. The cost of such private care is high. In this background, the voice activated cloud devices could play a significant role in the rehabilitation following a stroke.